Identification of Nematodes in Root System of Nutmeg (Myristica fragrans Hountt) in Dokulamo Village West Galela North Halmahera Regency - Mulyantana, Anang; Sunarno, Sunarno; Silelety, Angel (Agrikan Jurnal Agribisnis Perikanan, 2023)
Nematode s are plnat parasites that cause plant damage during most of their life cycle. This study aims to explore plant parasitic nematodes on the root system of nutmeg (Myristica fragrans Hountt). This research was conducted in Dokulamo Galela Barat Village, North Halmahera Regency from October to November 2022. This research consisted of two stages, namely sampling of nutmeg roots in the nutmeg plantation area and identification of nematodes on nutmeg roots using the Boerman method. The focus of this study was to identify the types of parasitic nematodes based on their morphological characteristics. The results showed that there were four types of parasitic nematodes that lived on nutmeg roots, namely Radhopolus sp., Meloidogyne sp., Rotylenchulus sp., and Pratylenchus sp